Progranulin (granulin/epithelin precursor) and its constituent granulin repeats repress transcription from cellular promoters - Hoque, Mainul (2010)
Progranulin (also known as granulin/epithelin precursor, GEP) is composed of seven granulin/epithelin repeats (granulins) and functions both as a full-length protein and as individual granulins. It is a secretory protein but a substantial amount of GEP is found inside cells, some in complexes with positive transcription elongation factor b (P-TEFb). GEP and certain granulins interact with the cyclin T1 subunit of P-TEFb, and with its HIV-1 Tat co-factor, leading to repression of transcription from the HIV promoter. We show that GEP lacking the signal peptide (GEPspm) remains inside cells and, like wild-type GEP, interacts with cyclin T1 and Tat. GEPspm represses transcription from the HIV-1 promoter at the RNA level. Granulins that bind cyclin T1 are phosphorylated by P-TEFb in vivo and in vitro on serine residues. GEPspm and those granulins that interact with cyclin T1 also inhibit transcription from cellular cad and c-myc promoters, which are highly dependent on P-TEFb, but not from the PCNA promoter. In addition, GEPspm and granulins repress transcriptional activation by VP16 or c-Myc, proteins that bind and recruit P-TEFb to responsive promoters. These data suggest that intracellular GEP is a promoter-specific transcriptional repressor that modulates the function of cellular and viral transcription factors.